Resistência de união e da microinfiltração marginal em restaurações fotopolimerizadas com LED e luz halógena associadas a três modos de aplicação de um sistema adesivo universal: estudo in vitro - Ricardi, Felipe de Brum (2017)
The objective was to evaluate the bond strength and marginal microleakage in composite resin restorations, using Universal Single Bond adhesive system associated with Ultralux (halogen) and Bluephase (LED) photoactivators. For bond strength, eighty healthy human third molars were divided: Halogen (n = 40); LED (n = 40), subdivided according to the technique of application of the adhesive system: self-etch – enamel; etch-and-rinse – enamel, self-etch – dentin; etch-and-rinse – dentin. The teeth were submitted to the Tensile Bond Strength test and the fracture pattern was observed under an optical microscope - 40X magnification, analyzed by the ANOVA, Tukey and Fisher tests (5%). For the marginal microleakage assay, 120 class II cavities were prepared in sixty healthy, randomly divided third human molars: Halogen (n = 30); LED (n = 30) and subdivided according to the application technique of the adhesive system: self-etch; selective-etch; etch-and-rinse. The teeth were thermocycled 2000 times (± 5 / 55ºC), stained in 5% basic fuchsin and sectioned for qualitative and quantitative evaluations, analyzed by the Kruskall-Wallis and Dunn tests (5%). For bond strength in enamel and dentin, the adhesive application with prior acid etching was better than the etch-and-rinse (p <0.0001), regardless of the type of photoactivator used (p <0.05). The self-etch showed the lowest values of microleakage, (p <0.0001). The self-etch, obtained the best results in relation to the other techniques of application of the adhesive system in both tests, regardless of the type of photoactivating apparatus.